Standard Functional Solution to The Problem of Positive Conflict of Nationalities - سليمان بتريسيا (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The study dealt with the research in the criterion of the functional solution as one of the non-traditional solutions in the problem of positive conflict of nationalities, as it is a modern theory that departs from the process of traditional legal treatment based on the traditional standards prevailing in jurisprudence and the judiciary, the most important of which is the criterion of the nationality of the judge and the criterion of actual nationality, where the study aimed to research the interaction of law Syrian with the problem of multiple nationalities, the definition and implementation of the theory of the functional solution and the most prominent criticisms leveled at him and the legal solutions that address these criticisms. This study reached many results, including: The problem of positive conflict of nationalities is one of the problems that creates negative effects that harm its owners, and the functional solution is one of the solutions that enjoy flexibility in finding a solution to this problem, and it is one of the modern theories in this field, by comparing it with the traditional theories related to Applying the law of the dispute judge when his nationality is among the conflicting nationalities, and applying the actual nationality law when the judge’s nationality is not among the nationalities. But it faces many practical difficulties for its application. The functional solution criterion is based on dealing with each issue as a preliminary issue linked to an original issue, so each issue is dealt with separately according to a provision that is consistent with the nature of the original issue in which the conflict of nationalities was presented. The functional solution criterion is a relative solution that differs from one issue to another, in light of the purpose or the nature of the relationship to which the original issue is connected, and varies from one country to another according to social, religious and demographic conditions, and this discrepancy creates constant concern in the legal status of the multinational individual, so he cannot know What is the law that will apply to this individual if he is not presented before any court in the world.